Sustainable Village Development: Overcoming The Challenges of Road Damage to Create a Prosperous Society - Dzilkamil, Khabibah; Adinugraha, Hendri Hermawan; Achmad, Dliyauddi; Andrean, Rizky; Sain, Zohaib Hassan (Prosperity: Journal of Society and Empowerment, 2024)
Sustainable Development Goals (SDGs) is a series of 17 internationally agreed development goals that aim to end poverty, protect the environment, and ensure that by 2030, all people can live in peace, prosperity, and harmony with the environment. This research aims to investigate the challenges faced in overcoming road damage in villages, as well as efforts that can be made to create sustainable solutions. It is also hoped that this research can provide a valuable contribution to addressing infrastructure problems at the local level and promoting positive transformation in village communities towards sustainable prosperity. This qualitative research uses descriptive methodology and data obtained through direct observation and data analysis in the form of a list of words. The people of Pandanarum Village find it difficult to access the road because there are several impassable points on the road, burdening the community with work and activities. Therefore, the Pandanarum Village Government has scheduled road asphalting, street lighting, and road drainage projects by village development which must be in line to implement the Sustainable Development Goals (SDGs) agenda to improve community welfare.